Trichomonas vaginalis Detection in Female Specimens with cobas(®) TV/MG for use on the cobas(®) 6800/8800 Systems - Marlowe, Elizabeth M. (Eur J Microbiol Immunol (Bp), 2019)
Trichomoniasis, a common curable sexually transmitted infection caused by the protozoan Trichomonas vaginalis (TV), is usually asymptomatic. However, symptomatic women may experience vaginal discharge and/or vulvar irritation. This study evaluated cobas(®) TV/ Mycoplasma genitalium (MG) (Conformité Européene marking for in vitro diagnostic medical devices [CE-IVD]) against other nucleic acid amplification tests (NAATs) for detecting TV in female urogenital specimens. Matched de-identified specimens from 412 females were collected. cobas(®) TV/MG results were compared against a composite reference (CR) of 3 different NAATs for TV (Aptima TV, modified S-DiaMGTV™, and a laboratory-developed test). The overall TV prevalence rate was 6.2%, based on cobas(®) TV/MG results. Relative to the CR, cobas(®) TV/MG sensitivity/specificity for the specimen types were endocervical swabs (ES) 100%/99.2%, vaginal swabs (VS) 100%/99.7%, urine (U) 100%/99.7%, and cervical specimens in PreservCyt(®) solution (PC) 100%/99.5%. There was no significant statistical difference between clinician-collected and self-collected VS (p = 0.28). Correlation of cobas(®) TV/MG vs. Aptima TV demonstrated the following positive, negative, and overall percent agreements, respectively: ES 69.0%, 98.7%, and 96.6%; VS 88.9%, 99.5%, and 98.8%; U 100%, 100%, and 100%; and PC 95.5%, 99.0%, and 98.8%. Detection of TV with cobas(®) TV/MG for use on the cobas(®) 6800/8800 systems demonstrated excellent performance in female urogenital specimens (overall sensitivity/specificity of 100%≥99.2%).